Synthesis, Characterization, and Antibacterial Activity Test of Chitosan–Nanosilver–Black Cumin Seed Oil (Nigella sativa) Gel Preparation against Staphylococcus aureus Bacteria - Mohammad Nurul Mustofa; Sari Edi Cahyaningrum (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The skin is the outermost organ of the human body and functions as a protective barrier against environmental factors, making it susceptible to wounds caused by physical trauma and microbial infections. One pathogenic bacterium frequently associated with skin disorders such as boils, acne, and wound infections is Staphylococcus aureus. Therefore, topical formulations are required to prevent and manage infection. The combination of chitosan, nanosilver, and black cumin oil exhibits antibacterial activity and biocompatibility. This study aimed to evaluate the characteristics and antibacterial activity of a chitosan–nanosilver–black cumin oil gel against Staphylococcus aureus. The gel was formulated in five variations containing black cumin oil concentrations of 3%, 4%, 5%, 6%, and 7%. Chemical characterization was performed using Fourier Transform Infrared spectroscopy to identify functional groups, while nanosilver particle size was analyzed using a Particle Size Analyzer. Physical evaluation included a pH measurement to assess compatibility with the skin's pH. Antibacterial activity was determined by the disc diffusion method, measuring inhibition zone diameters. The Particle Size Analyzer results showed an average nanosilver particle size of 31.54 nm. FTIR analysis of the chitosan–nanosilver system confirmed the presence of O–H, N–H, C–H, and C=O functional groups, while FTIR characterization of black cumin oil confirmed the presence of functional groups associated with C–H stretching, C=O, C–O, and =C–H bending. The formulated gel exhibited a pH of 5.12–5.72, within the physiological pH range of human skin. Antibacterial testing demonstrated that inhibitory activity increased with increasing black cumin oil concentration, with the largest inhibition zone observed in the 7% formulation (21.67 mm). These findings indicate that chitosan–nanosilver–black cumin oil gel has potential for development as an antibacterial formulation.